A longitudinal study of the relationships between the Big Five personality traits and body size perception. (June 2015) - Hartmann, Christina; Siegrist, Michael
Highlights: Personality traits are longitudinally associated with body size perceptions. Neuroticism predicts a larger perceived body size in women over time. Conscientiousness predicts a thinner perceived body size in both genders over time. Abstract: The present study investigated the longitudinal development of body size perception in relation to different personality traits. A sample of Swiss adults ( N  = 2905, 47% men), randomly selected from the telephone book, completed a questionnaire on two consecutive years (2012, 2013). Body size perception was assessed with the Contour Drawing Rating Scale and personality traits were assessed with a short version of the Big Five Inventory. Longitudinal analysis of change indicated that men and women scoring higher on conscientiousness perceived themselves as thinner one year later. In contrast, women scoring higher on neuroticism perceived their body size as larger one year later. No significant effect was observed for men scoring higher on neuroticism. These results were independent of weight changes, body mass index, age, and education. Our findings suggest that personality traits contribute to body size perception among adults.